2015
DOI: 10.1093/pcp/pcv124
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Profiles Reveal Sugar and Hormone Signaling Pathways Mediating Flower Induction in Apple (Malus domesticaBorkh.)

Abstract: Flower induction in apple (Malus domestica Borkh.) is regulated by complex gene networks that involve multiple signal pathways to ensure flower bud formation in the next year, but the molecular determinants of apple flower induction are still unknown. In this research, transcriptomic profiles from differentiating buds allowed us to identify genes potentially involved in signaling pathways that mediate the regulatory mechanisms of flower induction. A hypothetical model for this regulatory mechanism was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 73 publications
12
124
2
Order By: Relevance
“…Previous studies have shown that endogenous hormones, nucleic acids, carbohydrates, and proteins also affect flower induction. Leaves are the main organs for producing nutrients in the plant and are the main source of nutrients for flower induction [29,30,31]. In the present study, we found significant differences in fresh weight, dry weight, and leaf area among the three materials, indicating that these attributes were affected by grafting.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have shown that endogenous hormones, nucleic acids, carbohydrates, and proteins also affect flower induction. Leaves are the main organs for producing nutrients in the plant and are the main source of nutrients for flower induction [29,30,31]. In the present study, we found significant differences in fresh weight, dry weight, and leaf area among the three materials, indicating that these attributes were affected by grafting.…”
Section: Discussionsupporting
confidence: 49%
“…The experiment was repeated three times. The detailed methods of raw fastq files handling from RNA-seq were carried out according to Xing [68]. …”
Section: Methodsmentioning
confidence: 99%
“…Flower induction was affected by environmental and internal factors (Guitton et al, 2012; Xing et al, 2014, 2015; Fan et al, 2016). Sugar and hormones were involved in flower induction (Guitton et al, 2012; Xing et al, 2014, 2015; Fan et al, 2016; Li et al, 2016; Zhang et al, 2016). Among all kinds of hormones, including auxin, cytokinins, abscisic acid, GA and other hormones.…”
Section: Introductionmentioning
confidence: 99%
“…GA was defined the most important hormones in regulating flower induction and GA pathway was recognized as one of the flowering pathways (Guitton et al, 2012; Porri et al, 2012; Li et al, 2016; Zhang et al, 2016). 6-BA and sucrose, which can promote flower bud differentiation, were also important and widely used (Xing et al, 2015; Li et al, 2016). Several flowering-related genes families have been identified and characterized in the apple genome, including SPL, IDD , and MADX-box (Li et al, 2013; Kumar et al, 2016; Fan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%